Online purchasing behavior: a systematic review - Şahin, Aybüke İrem; Öztürk, İrem; Dirik, Gülay (Journal of Dependence, 2024)
The shopping process has gained a new dimension with introduction of the internet into our lives and the phenomenon of online shopping has emerged. Online shopping has become a more preferred channel than traditional shopping. This situation exposes us to a new risk of addiction. The aim of the current study is to review research articles examining online shopping behavior. Studies on online shopping behavior conducted between 2017-2023 were scanned from Scopus, Pubmed, Ekual and TRDizin databases. 84 articles were reached as a result of the search. After following the PRISMA steps, 12 studies were identified to be included in the review. During viewing process, it was found that the concept of online shopping behavior was defined differently by different researchers. In this context, the studies were divided into 3 categories according to their definitions: online compulsive shopping, problematic internet shopping and online shopping addiction. Social support was found to be the most commonly considered variable as a protective factor for online shopping behavior. Adjustment disorder, social media use, dissociation, impulsivity and alexithymia symptoms, anxious attachment and low self-esteem were found to be risk factors for online shopping bahevior. In the light of the current findings, the prevention and intervention of problematic internet shopping behavior can be developed.
Keywords: Addiction; compulsive online shopping; online shopping behavior; online buying; problematic internet shopping